Focus, Intensity, and Tenacity (FIT) Training: A relapse prevention-based intervention to stop the downward spiral. Issue 1 (2nd January 2016) - Shoenfelt, Elizabeth L.
Abstract: Relapse prevention (RP) training prepares individuals to self-manage behavior to respond appropriately in high-risk situations. FIT (Focus, Intensity, and Tenacity) Training, an RP-based intervention, is designed to prevent or stop relapse into negative self-talk that can lead to the downward spiral. Athletes identify situational triggers and appropriate behavioral and cognitive responses to challenging situations to help ensure optimal performance. An example of successfully implementing FIT Training with a high-potential team is presented. RP/FIT Training can serve as an important intervention to prevent/stop relapse and to ensure the successful transfer of mental skills in competitive situations.